Cefazolin high-inoculum effect in methicillin-susceptible Staphylococcus aureus from South American hospitals (2013)
Objectives Clinical failures with cefazolin have been described in high-inoculum infections caused by methicillin-susceptible Staphylococcus aureus (MSSA) producing type A β-lactamase. We investigated the prevalence of the cefazolin inoculum effect (InE) in MSSA from South American hospitals, since cefazolin is used routinely against MSSA due to concerns about the in vivo efficacy of isoxazolyl penicillins. Methods MSSA isolates were recovered from bloodstream (n = 296) and osteomyelitis (n = 68) infections in two different multicentre surveillance studies performed in 2001–02 and 2006–08 in South American hospitals. We determined standard-inoculum (105cfu/mL) and high-inoculum (107 cfu/mL) cefazolin MICs. PFGE was performed on all isolates that exhibited a cefazolin InE. Multilocus sequence typing (MLST) and sequencing of part of blaZ were performed on representative isolates. Results The overall prevalence of the cefazolin InE was 36% (131 isolates). A high proportion (50%) of MSSA isolates recovered from osteomyelitis infections exhibited the InE, whereas it was observed in 33% of MSSA recovered from bloodstream infections. Interestingly, Ecuador had the highest prevalence of the InE (45%). Strikingly, 63% of MSSA isolates recovered from osteomyelitis infections in Colombia exhibited the InE. MLST revealed that MSSA isolates exhibiting the InE belonged to diverse genetic backgrounds, including ST5, ST8, ST30 and ST45, which correlated with the prevalent methicillin-resistant S. aureus clones circulating in South America. Types A (66%) and C (31%) were the most prevalent β-lactamases. Conclusions Our results show a high prevalence of the cefazolin InE associated with type A β-lactamase in MSSA isolates from Colombia and Ecuador, suggesting that treatment of deep-seated infections with cefazolin in those countries may be compromised.